The Use of Instagram to Develop Students’ Vocabulary Mastery - Mukolo, Magfira; Tuerah, Ignatius J. C.; Rorimpandey, Rinny S (Program Studi Pendidikan Bahasa Inggris, 2024)
This study investigated the impact of using Instagram Reels on students' vocabulary acquisition, focusing on everyday vocabulary related to verbs, nouns, and adjectives. The research applied a quantitative design to measure performance before and after the intervention, targeting 22 students from the 7th grade of SMP Negeri 1 Remboken. Results revealed a significant development, with mean scores rising from 23.485 to 39.09, demonstrating a 66.44% enhancement in performance. These findings underscore the effectiveness of Instagram Reels as a dynamic educational tool, offering a more engaging and efficient learning experience. The substantial development advocates for the adoption of innovative teaching strategies, highlighting the role of social media in enriching educational methodologies. By integrating Instagram Reels into educational practices, educators can create a more stimulating and interactive learning environment. This approach not only enhances vocabulary acquisition but also promotes better engagement and motivation among students. Embracing such innovative strategies can significantly develop overall learning outcomes and better prepare students for the diverse and evolving challenges of contemporary education.